Research on mapping technology of laser navigation robot without reflector - Haiying, Zhang; Shengming, Liu; Zhiying, Jiang (Journal of physics. Conference series, 2020)
In view of the problems existing in the construction of large sparse environment map for laser navigation robot without reflector, an incremental SLAM algorithm based on multistage ICP matching is proposed. This method constructs a new image according to the pose of the robot, and develops a regional closed-loop algorithm combined with incremental optimization method based on the graph optimization algorithm. Experimental results show that due to the low amount of environmental information, the algorithm can effectively avoid falling into local minima, eliminate the cumulative error of mapping, reduce the computational complexity, and realize accurate mapping and real-time application.